Adsorption of cadmium from aqueous solutions by novel Fe3O4- newly isolated Actinomucor sp. bio-nanoadsorbent: functional group study. (12th November 2018) - Masoudi, Ramin; Moghimi, Hamid; Azin, Ehsan; Taheri, Ramezan Ali
Abstract: A novel bio-nanocomposite was prepared by the combination of fungal biomass and Fe3 O4 magnetic nanoparticles. The result of XRD and EDAX analysis indicated that Fe3 O4 Actinomucor sp. bio-nanoadsorbent was prepared. Our experiments showed that the adsorption kinetics and isotherm of this material comply with the pseudo-second-order and the Langmuir models, respectively. The maximum adsorption capacity ( qmax ) of this novel bio-nanoadsorbent was obtained as 29.49 mg/g. The thermodynamic analysis revealed that the adsorption of Cd 2+ is spontaneous and exothermic. The optimum temperature, initial concentration, contact time and pH for adsorption system of cadmium were about 45 °C, 400 mg/L, 120 min and 7, respectively. Pretreatment of adsorbent by NaOH and SDS significantly increased cadmium adsorption capacity. SEM images showed that Fe3 O4 nanoparticles were immobilized successfully on the fungus cell surface. Contribution of the carboxyl, hydroxyl, amine and Fe–O functional groups of the bio-nanoadsorbent in the binding to cadmium ions was revealed by FTIR analysis. Results from regeneration studies indicated reusability of the adsorbent up to 91%. According to experimental results, it could be claimed that bio-nanocomposite of Fe3 O4 − Actinomucor sp. is a novel efficient adsorbent for removal of metal ions from aqueous solutions, and hence it has potential to be used in the environmental pollution cleanup programs.